2014
DOI: 10.1248/bpb.b13-00641
|View full text |Cite
|
Sign up to set email alerts
|

Development of Strain-Specific PCR Primers for Quantitative Detection of <i>Bacillus mesentericus</i> Strain TO-A in Human Feces

Abstract: Strain-specific polymerase chain reaction (PCR) primers for detection of Bacillus mesentericus strain TO-A (BM TO-A) were developed. The randomly amplified polymorphic DNA (RAPD) technique was used to produce potential strain-specific markers. A 991-bp RAPD marker found to be strain-specific was sequenced, and two primer pairs specific to BM TO-A were constructed based on this sequence. In addition, we explored a more specific DNA region using inverse PCR, and designed a strain-specific primer set for use in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It was also reported that B . subtilis TO-A produces bifidobacteria growth factors in the intestine and increases its amount [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that B . subtilis TO-A produces bifidobacteria growth factors in the intestine and increases its amount [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral probiotic preparations that contain Clostridium butyricum TO-A (CB), Enterococcus faecium T-110 (EF), and Bacillus subtilis TO-A (BS) exert beneficial effects on the health of hosts, including humans and livestock. Preparations containing these organisms have been utilized as probiotic drugs for treating intestinal diseases such as constipation, diarrhea, irritable bowel syndrome, enteritis, and other infectious diseases for more than 50 years [ 4 , 5 , 6 , 7 , 8 ]. In addition, it was recently suggested that these probiotic bacteria could reduce the risk of recurrent spontaneous preterm delivery in pregnant women [ 9 ].…”
Section: Introductionmentioning
confidence: 99%